Loss of prdm1a accelerates melanoma onset and progression. Issue 9 (20th June 2020) - Iwanaga, Ritsuko; Truong, Brittany T.; Hsu, Jessica Y.; Lambert, Karoline A.; Vyas, Rajesh; Orlicky, David; Shellman, Yiqun G.; Tan, Aik‐Choon; Ceol, Craig; Artinger, Kristin Bruk
Abstract: Melanoma is an aggressive, deadly skin cancer derived from melanocytes, a neural crest cell derivative. Melanoma cells mirror the developmental program of neural crest cells in that they exhibit the same gene expression patterns and utilize similar cellular mechanisms, including increased cell proliferation, epithelial‐mesenchymal transition, and migration. Here we studied the role of neural crest regulator PRDM1 in melanoma onset and progression. In development, Prdm1a functions to promote neural crest progenitor fate, and in melanoma, we found that PRDM1 has reduced copy number and is recurrently deleted in both zebrafish and humans. When examining expression of neural crest and melanocyte development genes, we show that sox10 progenitor expression is high in prdm1a −/− mutants, while more differentiated melanocyte markers are reduced, suggesting that normally Prdm1a is required for differentiation. Data mining of human melanoma datasets indicates that high PRDM1 expression in human melanoma is correlated with better patient survival and decreased PRDM1 expression is common in metastatic tumors. When one copy of prdm1a is lost in the zebrafish melanoma model Tg(mitfa:BRAF V600E ); p53 −/− ; prdm1a +/−, melanoma onset occurs more quickly, and the tumors that form have a larger area with increased expression of sox10 . These data demonstrate a novel role for PRDM1 as a tumor suppressor in melanoma.